مولانا حميد الدين فراہی اور جمہور علماء کے نزديك اصولِ تاویل: Principles of Interpretation according to Maul┐n┐ ╓am┘d Udd┘n Far┐h┘ and mainstream of Scholars (Khairulummah, 2022)
This article aims to explore the principles of interpretation introduced by mainstream of scholars and Maulana Hameed Uddin Far┐h┘. His exegesis Ni╘┐m ul Qur'┐n is based on the principles introduced by him. It is undeniable fact that Qur'┐n is a treasure of wisdom and ocean of knowledge. The more a diver dives into the layers of this ocean, the more he benefits from the precious jewels. The verses of the Qur'┐n have been considered in every age but there are some words and verses in the Qur'an having multiple or unclear meaning which are known as Mutash┐bih┐t. The interpreters have tried their best to determine its meaning considering its context etc., but Maulana Hameed Uddin Fahari introduced some new principles for the purpose and classified it into three types i.e., Primary principles, Probabilistic Principles, and baseless principles. According to Maulana Far┐h┘ the latter is not a principle by itself, but he has mentioned it only to avoid it. The present article discusses it in detail.